2012
DOI: 10.7314/apjcp.2012.13.7.3325
|View full text |Cite
|
Sign up to set email alerts
|

Glulathione-S-transferases Gene Polymorphism in Prediction of Gastric Cancer Risk by Smoking and Helicobacter Pylori Infection Status

Abstract: Aim: To evaluate the association of glutathione S-transferases gene polymorphisms with the risk of gastric cancer, with reference to smoking and Helicobacter pylori infection. Methods: We conducted a 1:1 matched casecontrol study with 410 gastric cancer cases and 410 cancer-free controls. Polymorphisms of GSTM1, GSTT1 and GSTP1 were determined using PCR-CTPP. Results: The GSTM1 and GSTT1 null genotypes were significantly associated with the risk of gastric cancer after adjusting for potential confounding facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…The allele frequencies for all the studied GSTs polymorphisms were similar to those reported from Chinese population (Jing et al, 2012;Song et al, 2012). However, the sample size is relative small in our study, and statistical power is insufficient for detecting the effect of GSTs genes on AML risk.…”
Section: Discussionmentioning
confidence: 54%
“…The allele frequencies for all the studied GSTs polymorphisms were similar to those reported from Chinese population (Jing et al, 2012;Song et al, 2012). However, the sample size is relative small in our study, and statistical power is insufficient for detecting the effect of GSTs genes on AML risk.…”
Section: Discussionmentioning
confidence: 54%
“…The pathogen has a strong association with a variety of gastric pathologies, including type B antral gastritis, peptic ulcer, gastric MALT lymphoma, and gastric adenocarcinoma (Jing et al, 2012). It is consider that H. pylori infection is the most common cause of morbidity and mortality in upper digestive tract diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The GSTM1 null genotype was found to be high in stomach cancer cases (55.9%) as compared to healthy neighborhood controls (47.5%), although this difference was not statistically significant. Another three studies carried out in China (Cai et al, 2001;Jing et al, 2012) and Japan (Katoh et al, 1996) also reported high frequency of GSTM1 null genotype among stomach cancer cases than in controls. GSTT1 homozygous null genotype was 36.3% in cases and 45.6% in controls which difference was also not significant.…”
Section: Discussionmentioning
confidence: 92%
“…Although several meta-analyses revealed a strong relationship between H. pylori and gastric cancer (Eslick et al, 1999;Xue et al, 2001), it is still controversial in different Asian countries (Miwa et al, 2002;Jing et al, 2012). Various studies from India also failed to show an association between H. pylori infection and gastric cancer (Kate et al, 2000;Khanna et al, 2002;Singh et al, 2006).…”
Section: Discussionmentioning
confidence: 99%